Cerebrovascular complications associated with infective endocarditis and anticoagulant treatment strategies - XIAOKAITIJIANG Muhetaer; ZHAO Feng (Chinese Journal of Contemporary Neurology and Neurosurgery, 2024)
Infective endocarditis often leads to various vascular complications, among which cerebrovascular complications are associated with increased mortality in the early and late stages of the disease. Anticoagulant therapy for infective endocarditis is still controversial. How to balance the risk of cerebral embolism and bleeding events during the treatment is a difficult problem to define in clinical practice. This article reviews the epidemiology, pathophysiology, imaging evaluation methods and anticoagulation treatment strategies of disease⁃related cerebral embolism and bleeding events, in order to provide guidance for clinical anticoagulant treatment of infective endocarditis.